2021
DOI: 10.1002/onco.13810
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Cemiplimab, Radiotherapy, Cyclophosphamide, and Granulocyte Macrophage Colony-Stimulating Factor in Patients with Recurrent or Metastatic Head and Neck Squamous Cell Carcinoma

Abstract: Background. Refractory and metastatic (R/M) head and neck squamous cell carcinoma (HNSCC) generally does not respond to PD-1 inhibitor monotherapy. Cemiplimab is a human anti-PD-1 monoclonal antibody. An expansion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Another case report innovatively used triple-combination therapy in esophageal squamous cell carcinoma (ESCC) and obtained short-term benefits, but the patient died of severe pneumonia ( 43 ). A Phase I trial of cemiplimab, radiotherapy, cyclophosphamide, and GM-CSF in patients with recurrent or metastatic head and neck squamous cell carcinoma, did not demonstrate higher efficacy than other PD-1 inhibitor monotherapies but showed tolerability of the regimen, and the most common treatment-emergent adverse events (TEAEs) included fatigue (40%), constipation (26.7%), asthenia, dyspnea, maculopapular rash, and pneumonia (20% each) ( 44 ). The SWORD trial reported the preliminary results of feasibility and safety of the triple combination of a PD-1/PD-L1 inhibitor, SBRT and GM-CSF in advanced solid tumors ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another case report innovatively used triple-combination therapy in esophageal squamous cell carcinoma (ESCC) and obtained short-term benefits, but the patient died of severe pneumonia ( 43 ). A Phase I trial of cemiplimab, radiotherapy, cyclophosphamide, and GM-CSF in patients with recurrent or metastatic head and neck squamous cell carcinoma, did not demonstrate higher efficacy than other PD-1 inhibitor monotherapies but showed tolerability of the regimen, and the most common treatment-emergent adverse events (TEAEs) included fatigue (40%), constipation (26.7%), asthenia, dyspnea, maculopapular rash, and pneumonia (20% each) ( 44 ). The SWORD trial reported the preliminary results of feasibility and safety of the triple combination of a PD-1/PD-L1 inhibitor, SBRT and GM-CSF in advanced solid tumors ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CTLA-4 inhibitors monotherapy as well as combination therapy with CTLA-4 inhibitors and either gemcitabine or cyclophosphamide showed promising results in BC and also CRC mouse models [89]. The phase 1 clinical trial of 15 patients with refractory and metastatic HNSCC showed that combination therapy of cyclophosphamide and radiation therapy in combination with GM-CSF (granulocyte macrophage-colonystimulating factor) could demonstrate significant therapeutic benefit [90]. Recent research demonstrated that treatment with PD-L1 and CTLA-4 inhibitors in conjunction with cancer stem cell-pulsed dendritic cells (CSC-DC) improved T cell proliferation, inhibited TGF-β secretion, intensified IFN-γ secretion, and improved host-specific CD8 + T cell response versus CSCs in B16-F10 mice melanoma tumour model [91].…”
Section: Ctla-4 Inhibitormentioning
confidence: 99%
“…Notwithstanding, some tumor-bearing mice advanced spontaneous metastases under continuous treatment with combined regimen [ 142 ]. Moreover, a phase 1 clinical trial in 15 patients with refractory and metastatic HNSCC indicated that combination therapy with PD-1 inhibitor cemiplimab plus cyclophosphamide, radiation therapy (RT), and granulocyte–macrophage colony-stimulating factor (GM-CSF) could demonstrate acceptable safety profile [ 143 ]. However, the regimen resulted in no significant effects compared to the monotherapy with cemiplimab.…”
Section: Combination Therapy Using Icismentioning
confidence: 99%